Faktor – Faktor Yang Mempengaruhi Siswa Memilih Program Keahlian Akuntansi di SMK Negeri 5 Gorontalo - Nur Aprilyani B. Luawo; Radia Hafid; Rierind Koniyo; Roy Hasiru; Sudirman Sudirman (STIKes Ibnu Sina Ajibarang, 2025)
This research examines the factors that influence students in choosing the Accounting Expertise Program at SMK Negeri 5 Gorontalo. This research aims to identify: what factors influence students in choosing the accounting expertise program at SMK Negeri 5 Gorontalo. Based on this research focus, this research aims to determine the specific factors affecting student's decisions to enroll in the Accounting Expertise Program at SMK Negeri 5 Gorontalo. The informants in this research consisted of the Head of the Accounting Study Program and ten 11th grade accounting students. This research employed a qualitative approach. Data collection was conducted through observation, interviews, and documentation. The collected data were analyzed using qualitative analysis techniques. The results indicate that several factors influence student's choice of the Accounting Expertise Program at SMK Negeri 5 Gorontalo. These include both internal and external factors, namely: interest, talent, motivation, family influence, job opportunity considerations, and economic factors. These factors are interrelated in shaping student's decisions.